2019
DOI: 10.1371/journal.ppat.1008100
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4 family ubiquitin ligases associate with LCMV Z’s PPXY domain and are required for virus budding, but not via direct ubiquitination of Z

Abstract: Viral late domains are used by many viruses to recruit the cellular endosomal sorting complex required for transport (ESCRT) to mediate membrane scission during viral budding. Unlike the P(S/T)AP and YPX(1–3)L late domains, which interact directly with the ESCRT proteins Tsg101 and ALIX, the molecular linkage connecting the PPXY late domain to ESCRT proteins is unclear. The mammarenavirus lymphocytic choriomeningitis virus (LCMV) matrix protein, Z, contains only one late domain, PPXY. We previously found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 115 publications
1
14
0
Order By: Relevance
“…The silencing of ITCH in LASV-infected A549 cells could be, in part, rescued by Nedd4, explaining why the extinction of ITCH expression had a greater effect on MOPV-infected cells. Our conclusions are in line with the work of Ziegler et al, as the silencing of ITCH decreased the proportion of LCMV VLPs released, and a compound preventing PPxY-Nedd4 interaction inhibited both LCMV and LASV Z VLPs release [66,70].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The silencing of ITCH in LASV-infected A549 cells could be, in part, rescued by Nedd4, explaining why the extinction of ITCH expression had a greater effect on MOPV-infected cells. Our conclusions are in line with the work of Ziegler et al, as the silencing of ITCH decreased the proportion of LCMV VLPs released, and a compound preventing PPxY-Nedd4 interaction inhibited both LCMV and LASV Z VLPs release [66,70].…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in accordance with a recent study in which authors showed that three Nedd4 family proteins (Nedd4, WWP1, and ITCH) bind the PPxY domain of LCMV and JUNV Z protein. Although this interaction resulted in ubiquitination of Z in transfection condition, Z ubiquitination was also dispensable for virus particle release [66].…”
Section: Discussionmentioning
confidence: 96%
“…Filoviruses (e.g., Ebola and Marburg [ 98 ]) and rhabdoviruses (e.g., vesicular stomatitis virus (VSV [ 99 ])) also encode a PPXY motif in their VP40 and M proteins, respectively, that specifically interacts with WW domain containing proteins to facilitate viral release. Arenaviruses also encode a PPXY domain in their matrix Z protein [ 100 ], through which the NEDD4 ligase is recruited [ 101 , 102 ]. However, ubiquitination of the PPXY-containing Z protein of LCMV itself is insufficient for virus budding, suggesting factors other than Z is involved [ 101 ].…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…Arenaviruses also encode a PPXY domain in their matrix Z protein [ 100 ], through which the NEDD4 ligase is recruited [ 101 , 102 ]. However, ubiquitination of the PPXY-containing Z protein of LCMV itself is insufficient for virus budding, suggesting factors other than Z is involved [ 101 ].…”
Section: Viral Factors Involved In Entry To the Escrt Pathwaymentioning
confidence: 99%
“…They demonstrated that these ligases ubiquitinate LCMV Z, a process that was dispensable for virus release but needed for defective interfering (DI) particle release. These data infer that ubiquitination of other cellular or viral targets than the Z protein by Nedd4 ligases may be the essential link to the ESCRT machinery and enhancement of viral budding [ 181 ]. Alongside ubiquitination as a regulator of viral budding, Ziegler and colleagues identified two phosphorylation sites, Y97 and S98 (LASV numbering), located at the C-terminal tail of protein Z and overlapping with the late domain region that could also influence Z protein function.…”
Section: Evasion Strategies Of the Arenavirus Matrix Protein Zmentioning
confidence: 99%